The Analysis of Nursing Students Needs in ESP Course - Setiyani, Solis; Dahlina, Ulinuha; Wahyuni, A'i; Nupus, Neng Ana Aprilya; Ramadhan, Ilham (JEDLISH : Journal Of Education and English Language Teaching, 2023)
Nowadays, the opportunity for nurses to work abroad is wider and even wider more by the commitments of 61 members of World Trade Organization (WTO) under the General Agreement on Trade in Services (GATS). This challenges non-English native universities with nursing study program to equip their graduates with English communication skill through English for Specific Purpose Course. This study aimed to find nursing students needs in learning English. It used a mixed-method research design with 45 nursing students selected purposively as the respondents. The data were collected through a questionnaire, class observations, and interviews. In the interviews, the researchers invited 10 of 45 students to answer several open questions. Then, the data were analyzed descriptively. The results produced three themes, namely: (1) reading and speaking skill: reality and expectation, (2) nursing student perspectives on English and the learning, and (3) ELT effectiveness with ESP approach. In practice field, the students found that they needed to understand the English reading texts and expected to have a better speaking skill. They also showed a high interest in English and felt the importance for their future career. They argued that their ongoing English learning was effective for them since the learning materials were suited and supporting media were available. Thus, the students stated readiness to implement their English communication skill in nursing occupational practices.